Gay Voluntary Associations in New York : Public Sharing and Private Lives - Shokeid, Moshe (Book collections on Project MUSE., 2014)
Gay Voluntary Associations in New York examines social groups and personal experiences in the LGBT population of New York City, including religious congregations and assemblies of senior, interracial, bisexual, and compulsive individuals, to shed light on their social discourse of sex, love, friendship, and spirituality.